Biofortification: A new approach to eradicate hidden hunger. Issue 1 (2nd January 2017) - Sharma, Priyanka; Aggarwal, Poonam; Kaur, Amarjeet
ABSTRACT: Low dietary diversity and major dependence on calorie rich diets are responsible for high malnutrition rates especially in Asian and African countries. Highlighting the actual cause to be sole dependence on staples for food, biofortification has emerged as a new tool to combat the widely distributed menace of hidden hunger. Biofortification promises the better nutritional accessibility to masses overcoming various hindrances and reaching the doorstep. This article discusses the various methods of biofortification and the pros and cons it offers. Consultative Group on International Agriculture Research (CGIAR) through its Harvest Plus program targeting to improve the nutritional status of the most affected regions of the world through biofortification. The orange fleshed sweet potato has proved to be a success in Africa while the golden rice is still under scruitinization.